DELAYS IN HEALTH INSURANCE CLAIMS AT A THIRD-PARTY ADMINISTRATOR (TPA) PT. XYZ IN 2024 - Wulandari, Reny Yulita; Purnamawati, Dewi (HEARTY, 2025)
Third-Party Administrators (TPA) play a crucial role in managing health insurance claims. However, delays in claim processing remain a major issue that negatively affects customer satisfaction. This study aims to describe the occurrence of delayed health insurance claims at one TPA in Indonesia in 2024. A descriptive quantitative approach was used, analyzing 442,279 secondary claim records to determine the frequency, type, and underlying causes of delayed claims. The findings revealed that 34% of all claims were classified as pending. Most pending claims involved outpatient and cashless services. The leading cause of the delay was incomplete documentation (55%), followed by invoice revisions and further claim investigations. These delays were largely attributed to unresolved administrative issues. Improving claim service quality in TPA requires the implementation of digital processing systems, enhanced staff competencies, and real-time document monitoring mechanisms.